Multiple hepatosplenic abscesses in an immunocompetent host - Hirapara, Jekishan J.; Bhende, Punam V.; Rangwala, Varin; Mannari, Jyoti G. (International Journal of Research in Medical Sciences, 2022)
Sphingomonas paucimobilis, a gram-negative organism, mainly infects immunocompromised hosts due to its low virulence. Patients with such an infection usually have contact with healthcare. Meningitis, peritonitis, visceral abscess, septic arthritis, septicemia, post-traumatic endophthalmitis, and keratitis are among the documented complications of Sphingomonas paucimobilis infection. Such an infection is rarely seen in the literature as the one causing splenic and liver abscess and that too in an immunocompetent host. We present a case of a 23-year-old immunocompetent male, who presented with fever and other constitutional symptoms with recent onset of abdominal pain and fullness. Splenic and liver abscesses were detected on radiology with the growth of only Sphingomonas on blood culture and negative reports for other organisms excluding the differentials, proving S.mobilis being the cause of the abscesses. The patient was managed on broad-spectrum antibiotics and additional medications for symptomatic relief. The patient gradually improved over 7 days of hospitalization. This case report mainly focuses on Sphingomonas paucimobilis infection, which is rarely seen and documented, and surprisingly in an immunocompetent host causing life-threatening infections and abscesses. Even though it’s a rare and a low virulence organism, such a presentation must not be overlooked. A regular and focused laboratory workup for detection and management, with adequate antibiotic treatment, is a must to avoid a poor prognosis.